Relationship between Clinicopathological Features and Expression of COX-2 among Colorectal Cancer Patients: A Prospective Observational Study - Mohamad Romdhoni; Kiki Lukman; Reno Rudiman; Andriana Purnama; Bambang Am'am Setya Sulthana Degrees; Tommy Ruchimat; Alma Wijaya; Yunia Sribudiani Degrees; Prapanca Nugraha (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Colorectal cancer (CRC) is the third most common cancer globally and a leading cause of cancer-related mortality. Cyclooxygenase-2 (COX-2) plays a critical role in CRC pathogenesis by promoting inflammation, tumor proliferation, and metastasis. COX-2 inhibitors, such as NSAIDs, have shown potential in reducing CRC progression. However, the relationship between COX-2 expression and clinicopathological features remains controversial. This study aims to assess the correlation between COX-2 expression and clinicopathological characteristics in CRC patients in Indonesia. A prospective observational study was conducted on 81 CRC patients at a tertiary hospital in West Java, Indonesia, from January to June 2024. COX-2 expression was quantified using qPCR from tumor tissue samples. Clinicopathological data, including age, sex, tumor grade, stage, and complications, were collected and analyzed. Among the 81 participants, 81.5% were over 50 years old. Low-grade adenocarcinoma was the most prevalent histopathological type (73%), followed by high-grade adenocarcinoma (11%) and mucinous adenocarcinoma (11%). The majority of cases were in regional or early stages (74%), while 26% were in late stages. Higher COX-2 expression was more frequent in males, rectal tumors, high- grade adenocarcinomas, advanced stages, and metastatic cases. Although no statistically significant association was found, a trend toward increased COX-2 expression in advanced CRC was observed. No significant association was found between COX-2 expression and clinicopathologic characteristics of CRC. However, higher COX-2 expression may be associated with advanced disease. Keyword: Clinicopathological features, Colorectal cancer, Cyclooxygenase-2, Inflammation, Metastasis